Two new easy to use vectors for transformations - P. Silar (Fungal Genetics Reports, 1995)
Several vectors containing dominant antibiotic resistance markers for the transformation of filamentous fungi are available. However, most of them lack a recombinant selection system and a polylinker containing a sufficient number of cloning sites, thereby limiting the subcloning strategies. I have constructed two new vectors, derived from the pBC-SK+ bluescript vector (Stratagene), that possess these characteristics as well as many other interesting features. The restriction maps and the available cloning sites of both plasmids are presented in Figure 1. Transformants in bacteria are selected on chloramphenicol-containing medium. Recombinants can be screened by using the blue/white selection associated with the lacZ system. The polylinkers of both plasmids contain numerous unique cloning sites and are flanked by two BssHII sites as well as T3 and T7 promoters for RNA production. The plasmids display unaltered f1 origins for the recovery of single-stranded DNA for sequencing or mutagenesis.